Penerapan Metode KNN-Regresi dan Multiplicative Decomposition untuk Prediksi Data Penjualan pada Supermarket X - Calvin Christopher Kurniawan; Silvia Rostianingsih; Leo Willyanto Santoso (Jurnal Infra, 2022)
Supermarket X is one of the supermarkets in West Nusa Tenggara that needs a way to predict sales in the future. This prediction is needed by Supermarket X to estimate the purchase plan because so far there have been frequent stockouts or oversupply which have caused losses to the company. Based on the problems that occur, this study applies the KNN Regression and Multiplicative Decomposition methods in predicting Supermarket X sales so that supermarket managers can design a strategy to make sales in the future. The results show that predictions based on divisions, departments, categories, sub categories, and products have a smaller average error rate when using the Multiplicative Decomposition method with RMSE = 492.89 and MAPE = 0.29, while the KNN Regression method has RMSE= 757.77 and MAPE= 0.36